EMAS recommendations for conditions in the workplace for menopausal women - Griffiths, Amanda; Ceausu, Iuliana; Depypere, Herman; Lambrinoudaki, Irene; Mueck, Alfred; Pérez-López, Faustino R.; van der Schouw, Yvonne T.; Senturk, Levent M.; Simoncini, Tommaso; Stevenson, John C.; Stute, Petra; Rees, Margaret (Elsevier, 2016)
Women form a large part of many workforces throughout Europe. Many will be working throughout their menopausal years. Whilst the menopause may cause no significant problems for some, for others it is known to present considerable difficulties in both their personal and working lives. During the menopausal transition women report that fatigue and difficulties with memory and concentration can have a negative impact on their working lives. Furthermore, hot flushes can be a source of embarrassment and distress. Some consider that these symptoms can impact on their performance. Greater awareness among employers, together with sensitive and flexible management can be helpful for women at this time. Particular strategies might include: fostering a culture whereby employees feel comfortable disclosing health problems, allowing flexible working, reducing sources of work-related stress, providing easy access to cold drinking water and toilets, and reviewing workplace temperature and ventilation.